The Role of E-Books in Improving Learning Achievement of Integrated Islamic Junior High School Students - Nuraini, Rini; Barroso, Uwe; Mukarromah, Indah; Intes, Amina; Khoir, Qoidul (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
At this time the world of education has depended on technology and the internet, all education personnel utilize technology as a tool in the teaching and learning process. Likewise, the role of E-books in improving student achievement at school at this time. The purpose of this study was to determine the role of E-books in improving student achievement by applying E-book media as an innovative learning media. The type of research method used is a quantitative method with a survey model and distributes online-based questionnaires via google form. Researchers hope that the results of the research conducted can increase student understanding through the E-book platform as a support in improving learning achievement. The conclusion of this study is that the role of E-books for students can help in improving student learning achievement. Therefore, the limitation of this research is that researchers only conduct online surveys and are not conducted thoroughly only in certain schools, researchers hope that future researchers can conduct research in other schools to make it more effective and efficient.